Methods of Interpretation: Mutlaq and Muqayyad - Ririn Ristiani; Alwizar Alwizar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This research aims to examine the application of mutlaq and muqayyad interpretation methods in understanding the verses of the Qur'an accurately, systematically and contextually. The methods of mutlaq and muqayyad are important instruments in the discipline of interpretation and ushul fiqh which also function to maintain the accuracy of the meaning and accuracy of the exploration of Islamic law..This study uses a qualitative approach with a library research method, namely reviewing and analyzing various literature sources in the form of books, tafsir books, and scientific journal articles relevant to the study theme. The results of the study indicate that mutlaq is a word that shows the ultimate meaning without any limitations of nature, size, or certain conditions, while muqayyad is a word that is limited by certain properties, circumstances, or conditions that bind its meaning.These two rules refer to the way the pronunciations in the Al-Quran are viewed in terms of the meaning they carry. Understanding these two rules is very important for mufassir and mujtahid in the istinbath al-ahkam process so that there are no misinterpretations of the text of the Al-Qur'an. Thus, mastering the methods of interpretation of mutlaq and muqayyad is the key to understanding the Al-Qur'an comprehensively and in accordance with the objectives of Islamic law. This study is expected to make an academic contribution to the development of contemporary Islamic interpretation and education studies in higher education.